2014
DOI: 10.1155/2014/457937
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Comprehensive Quality Index of Tomato under Rain Shelters in Response to Different Irrigation and Drainage Treatments

Abstract: The effects of two levels of irrigation water (100%, 60%) and buried underground pipe depths (0.8 m, 0.6 m) under rain shelters' conditions on yield and some quality parameters of tomato were investigated. A fully randomized factorial experiment was conducted between April and August in 2011 and 2012 at Hohai University. It was found that drainage treatments enhanced biomass production, whereas soil desiccation led to biomass reduction. At 60 cm buried underground pipe depths, the drought treatments increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…A number of studies have reported a reduction in tomato plant height especially under low rainfall (Dry, 1998). The reduction in plant height is a common phenomenon among plants that are sensitive to moisture stress, as a result of low rainfall (Shao, 2014). In tomato, the roots are severely affected by low soil moisture due to reduced root permeability and hydraulic conductivity, which in turn affects uptake and transport of nutrients supplied by fertilizers (Huang, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported a reduction in tomato plant height especially under low rainfall (Dry, 1998). The reduction in plant height is a common phenomenon among plants that are sensitive to moisture stress, as a result of low rainfall (Shao, 2014). In tomato, the roots are severely affected by low soil moisture due to reduced root permeability and hydraulic conductivity, which in turn affects uptake and transport of nutrients supplied by fertilizers (Huang, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Hou [70] adopted the projection pursuit model to select the best drip irrigation scheme for crop. Other methods, such as principal component analysis, entropy weight coefficient model were also used for guiding the agricultural production [71]. The essence of these models was the same, namely realizing the reduction of high-dimensional data.…”
Section: Discussionmentioning
confidence: 99%
“…The quality indexes for the Principal Component Analysis (PCA) were also obtained from the SPSS software. The principal components of the quality indexes were extracted following the principle of “eigenvalue > 1, cumulative contribution rate > 80%” [48]. …”
Section: Methodsmentioning
confidence: 99%
“…According to Nahar and Gretzmacher [1], glucose, fructose, sucrose, malic acid, ascorbic acid and citric acid content increased significantly with water stress and sweetness of tomatoes and quality enhanced. Another finding suggested as decreased level of irrigation exerted beneficial effects upon fruit quality, mostly with respect to total soluble solid and soluble sugar contents [22].…”
Section: Effect Of Deficit Irrigation On Tomato Yield and Qualitymentioning
confidence: 99%